2016
DOI: 10.1002/stem.2281
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a in Adult Muscle Stem Cells Controls Skeletal Muscle Regeneration During Injury and Exercise Downstream of Fibroblast Growth Factor-2

Abstract: The expansion of myogenic progenitors (MPs) in the adult muscle stem cell niche is critical for the regeneration of skeletal muscle. Activation of quiescent MPs depends on the dismantling of the basement membrane and increased access to growth factors such as fibroblast growth factor-2 (FGF2). Here, we demonstrate using microRNA (miRNA) profiling in mouse and human myoblasts that the capacity of FGF2 to stimulate myoblast proliferation is mediated by miR-29a. FGF2 induces miR-29a expression and inhibition of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 66 publications
2
48
0
1
Order By: Relevance
“…MiRNAs that reside on polycistronic transcripts are processed with different efficiencies despite being co-transcribed (Chakraborty et al, 2012; Chaulk et al, 2014), which could explain the higher abundance of miR-501 compared with miR-362. We have recently described a similar phenomenon for the miR-29a/b cluster in mouse and human muscle cells (Galimov et al, 2016). We currently lack sufficient evidence to conclude that other miRNAs located in the Clcn5-2 intron also share the miR-362/-501 cluster.…”
Section: Discussionsupporting
confidence: 57%
“…MiRNAs that reside on polycistronic transcripts are processed with different efficiencies despite being co-transcribed (Chakraborty et al, 2012; Chaulk et al, 2014), which could explain the higher abundance of miR-501 compared with miR-362. We have recently described a similar phenomenon for the miR-29a/b cluster in mouse and human muscle cells (Galimov et al, 2016). We currently lack sufficient evidence to conclude that other miRNAs located in the Clcn5-2 intron also share the miR-362/-501 cluster.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, a subpopulation of Myf5 + cells from extraocular muscle expresses Sca1 and is adipogenic 50. In our study, we relied on a prospective isolation strategy to obtain MPs from skeletal muscle by FACS based on the absence of CD31, CD45, and Sca1 and the presence of alpha 7‐integrin, which results in highly pure myogenic cultures 35. Analysing both polyclonal and monoclonal cell cultures, we could not identify any MP subpopulation with adipogenic potential.…”
Section: Discussionmentioning
confidence: 90%
“…After incubation with fluorescent antibodies, pure populations of MPs and FAPs cells, respectively, were obtained using fluorescence‐activated cell sorting (FACS, BD FACSAria III, BD Biosciences, San Diego, CA, USA). Fibro/adipogenic progenitors were sorted based on positive staining for Sca1 and absence of staining for alpha 7‐integrin, CD31, and CD45,30 while MPs were sorted based on positive staining for alpha 7‐integrin and absence of Sca1, CD31, and CD45 35. For analysis of monoclonal cell colonies, single FAPs and MPs were sorted directly into 96‐well cell culture plates containing growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was also reported by Uezumi et al (2014) that mesenchymal progenitors were identified in the human skeletal muscle interstitium and could be isolated by using PDGFRα as a specific marker. A single miRNA may regulate a large number of target genes acting in a similar pathway, thus playing an important role in biological regulation (Galimov et al, 2016). Some researchers have reported that PDGFRα + muscle cells participate in HO formation (Wosczyna et al, 2012;Oishi et al, 2013;Agarwal et al, 2016Agarwal et al, , 2017, however, the mechanisms that direct these progenitor cells to initiate cartilage and bone formation are still unknown.…”
Section: Discussionmentioning
confidence: 99%